Bond strength and Weibull analysis of fiber posts luted with different cement types and mechanically aged - Lira dos Santos, Elis Janaina; Campos, Fernanda [UNESP]; Dantas, Alana Moura Xavier; Lira, Maria Luiza Lima Alves; Wandsher, Vinícius Felipe; Silva, Nathalia Ramos da; Valandro, Luiz Felipe; Souza, Rodrigo Othávio de Assunção (Taylor & Francis, 2021)
This study aimed to evaluate the influence of cement type and mechanical cycling on the push-out bond strength (σ) of fiber posts luted to root canals. Eighty bovine single-root teeth were prepared and the roots were included with chemically cured acrylic resin. The specimens were allocated into 8 groups (n = 10) considering the factors ‘cement’ (glass ionomer cement–GIC, resin reinforced glass ionomer cement–RRGIC, conventional dual-cure resin cement–CRC, and self-adhesive resin cement–SARC) and ‘mechanical cycling’ (non-aged and aged–mc). The fiber posts and roots dentin were treated according to the cement type and luted to root canals. Composite-cores were made for the groups submitted to mechanical cycling (1,000,000 cycles, 84 N, 4 Hz). Each root were cut into 4 disk-samples of 1.8 mm (thickness) and submitted to push-out testing. Data (MPa) were analyzed using two-way ANOVA, Tukey test (5%), and Weibull analysis. ANOVA revealed that cement (p < 0.001) was significant; however, the mechanical cycling had no effect on bond strength (p = 0.895). The CRC (4.36 ± 1.15 MPa), CRCmc (4.13 ± 0.75 MPa), GIC (4.29 ± 2.14 MPa), and GICmc (4.04 ± 1.18 MPa) groups showed higher (σ) than RRGIC (2.36 ± 1.00 MPa). Weibull Characteristic strength of the CRC and CRCmc were significantly higher than RRGICmc, and RRGIC. The mixed type of failure was the most common. Conventional dual-cure resin cement and glass ionomer cement presented higher push-out bond strength to root dentin regardless of mechanical cycling.
Keywords: bond strength; cementation; Fiber post; mechanical cycling; root dentine